Timber Tracking of Jacaranda copaia from the Amazon Forest Using DNA Fingerprinting - Capo, Lorena Frigini Moro [UNESP]; Degen, Bernd; Blanc-Jolivet, Celine; Tysklind, Niklas; Cavers, Stephen; Mader, Malte; Meyer-Sand, Barbara Rocha Venancio [UNESP]; Paredes-Villanueva, Kathelyn; Honorio Conorado, Eurídice Nora; García-Dávila, Carmen Rosa; Troispoux, Valérie; Delcamp, Adline; et al. (MDPI, 2024)
We investigated the utility of nuclear and cytoplasmic single nucleotide polymorphism (SNP) markers for timber tracking of the intensively logged and commercialized Amazonian tree Jacaranda copaia. Eight hundred and thirty-two trees were sampled (cambium or leaves) from 38 sampling sites in Bolivia, Brazil, French Guiana, and Peru. A total of 128 SNP markers (113 nuclear, 11 chloroplastic, and 4 mitochondrial) were used for genotyping the samples. Bayesian cluster analyses were carried out to group individuals into homogeneous genetic groups for tests to self-assign groups of individuals or individuals to their population of origin. Cluster analysis based on all the SNP markers detected seven main genetic groups. Genetic differentiation was high among populations (0.484) and among genetic groups (0.415), and populations showed a strong isolation-by-distance pattern. Self-assignment testing of the groups of individuals for all loci was able to determine the population origin of all the samples (accuracy = 100%). Self-assignment tests of individuals were able to assign the origin of 94.5%–100% of individuals (accuracy: 91.7%–100%). Our results show that the use of the 128 SNP markers is suitable to correctly determine the origin of J. copaia timber, and they should be considered a useful tool for customs and local and international police.
Keywords: forensics; illegal logging; Jacaranda copaia; SNP markers; timber tracking; tropical trees